2019
DOI: 10.3390/ma12213583
|View full text |Cite
|
Sign up to set email alerts
|

Silicalite-1 Layers as a Biocompatible Nano- and Micro-Structured Coating: An In Vitro Study on MG-63 Cells

Abstract: Silicalite-1 is a purely siliceous form of zeolite, which does not contain potentially harmful aluminum in its structure as opposed to ZSM-5 aluminosilicate types of zeolite. This paper reports on a study of a silicalite-1 film, deposited on a silicon Si(100) substrate, as a potential anti-corrosive and biocompatible coating for orthopaedic implants. Silicalite-1 film was prepared in situ on the surface of Si(100) wafers using a reaction mixture of tetrapropyl-ammonium hydroxide (TPAOH), tetraethyl-orthosilica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
2
8
1
Order By: Relevance
“…The contact angle values are summarized in Table 2. The contact angle estimated for SF-RT is in good agreement with the previously published value of SFs on the Si(100) substrate 31 . The relatively high value of WCA observed for SF-RT is caused by the enrichment of hydrophobic C-containing species on the outer surface of the sample, as observed by XPS (Table 1).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The contact angle values are summarized in Table 2. The contact angle estimated for SF-RT is in good agreement with the previously published value of SFs on the Si(100) substrate 31 . The relatively high value of WCA observed for SF-RT is caused by the enrichment of hydrophobic C-containing species on the outer surface of the sample, as observed by XPS (Table 1).…”
Section: Resultssupporting
confidence: 90%
“…While no decrease in the number of Saos-2 cells grown on all SF samples was found, the spreading of cells on all SF samples was slightly but significantly lower than on the reference GS and on stainless steel. Similarly, another study of ours, performed on a different osteosarcoma cell line (MG-63), showed a markedly lower spreading area without a lower density of cells grown on SF-RT than on the reference GS and on reference Si(100) substrates 31 . The lower spreading of both osteosarcoma cell lines grown on SF samples is in accordance with the lower spreading of the non-tumor osteoblastic cell line in the present study.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations